Comparison of the financial market conditions in Poland and selected countries during the pandemic and the Russian-Ukrainian war - Dorota Żebrowska-Suchodolska; Andrzej Karpio (Journal of Banking and Financial Economics (JBFE), 2023)
The initial period of the COVID-19 pandemic and the outbreak of the Russian-Ukrainian war had a significant impact on financial markets. The aim of the work is to analyse the behaviour of selected segments of the Polish financial market in the initial period of the pandemic and war. The research is based on two measures of risk, relative and absolute. The research covers the period from 24 February 2022 to 22 August 2022. The research focuses on segments of the Warsaw Stock Exchange through the analysis of the following indices: WIG, WIG20, mWIG40, sWIG80, NCIndex, industry indices, and the TBSP treasury bond market index. The Warsaw Stock Exchange indices are also compared using variation coeffi cients and standard deviations with indices of selected world stock exchanges. After the start of the war, declines in the Warsaw Stock Exchange occurred with a delay of over a month. They can be linked to specific EU actions in the area of sanctions against Russia. Both risk measures indicate a similar response to the main indices, which can be interpreted as the high level of development of the Warsaw Stock Exchange, as compared to other stock exchanges.
Keywords: C43; C49; D53; E44; G50; 330; capital market; financial market; COVID-19 pandemic; Russian-Ukrainian war; measures of risk; market indices